Analisis Potensi Kecelakaan Kerja Dengan Metode Job Safety Analysis Pada Pekerjaan Produksi Fiberglass di CV. Jaya Mandiri Sidoarjo - Muhammad Rifqi Naufal; Yayok Suryo Purnomo (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Companies as providers of various products are obliged to implement Occupational and Health guidance, this effort is made to avoid the risk of accidents and work-related illnesses. Work accidents are often related to negligence or disobedience to work safety rules by workers which is generally caused by the worker's minimal level of knowledge. This research uses observational analysis with an inductive analysis approach and data is processed using the JSA and HIRARC methods and uses observational analysis with a cross-sectional approach whose samples are production workers. The results show that there are 6 workers with low knowledge characteristics, 7 workers with medium knowledge, and 17 workers with high knowledge. In the attitude aspect, there are 4 workers with a low level, 1 worker with a medium level, and 25 workers with a high level. And in the behavioral aspect there are 6 low level workers, 1 medium level worker, and 23 high level workers. The results of the analysis of the activity of making buckets from fiberglass showed that there were 7 sources of danger including being scratched by a razor blade, slipping, being stabbed by a sharp splinter, being exposed to chemicals, the smell of chemicals, tripping while walking, being pricked by a sewing needle. From the results, 2 potential risks were obtained with low risk values, 5 potential risks with medium risk values, and 3 potential risks with high risk values